O trabalho docente na educação básica pública no município de Fortaleza: contradições que envolvem a busca por resultados - Sampaio, Telmano Rodrigues (2019)
The objective of the research is to understand the contradictions that involve the teaching work in public basic education in the municipality of Fortaleza, from 2013 to 2018, and the relationships that involve the search for results in this context. The bibliographical and documentary study is based on dialectical historical materialism. The official documents that guide education in Brazil and in the city of Fortaleza stand out because it understands that such documents can guide the eyes of the phenomenon so that one can discover the essence of the thing. In this way, it broadens the debate with the ontological rescue of the work category, the relation with the teaching work and the education. With this, he perceives the need to dialogue with theoreticians who discuss such questions nowadays, as a way to broaden the present study. It is worth emphasizing that work, a foundational category of social being, and education, are essential for understanding social reality and for understanding the complexities that are present in this debate. He argues that categories sprout to make history and that the tearing of the veil allows us to know such challenges and act upon them. In this sense, considering the concerns and questions that permeate the work of the teacher, amid the contradictions of the present moment, justifies the importance of investigating this theme. These questions lead to the search for answers that help in the understanding of how the exploitation of man by man is revealed, revealed by Marx in his works and what the reflexes with the teaching work in the city of Fortaleza. It concludes that in the municipality of Fortaleza, the teacher, in the midst of the multiple contradictions, undergoes a series of directions derived from educational policies, with which he learns to live together as: (of) training, control through appraisals, working conditions precarious, salary denied, persecution, sickness at work, violence, accountability and control.